(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the Frequency of stress hyperglycemia and Incident Diabetes Mellitus in patients presenting with Acute Coronary syndrome. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Coronary Care Unit of DHQ Teaching Hospital Nowshera and Qazi Hussain Ahmad Medical Complex (QHMC) Nowshera from January 2017 to June 2018. Materials and Methods: They were interviewed through a pre-designed research proforma after informed written consent. Random plasma glucose (RPG) and fasting plasma glucose (FPG) were performed. The diagnosis of the sub type of ACS was made using the acute changes of the ECG and Qualitative Cardiac Troponin tests. Results: A total of 278 ACS patients were enrolled I the present study. There were more male patients (56.8%) with ACS. The frequency of Diabetes was 51.8% (n, 144) as compared to non-diabetics 48.2% (n, 134) in ACS. The Frequency of Stress hyperglycemia using RPG levels was 70.5% (n, 196). Frequency of Incident DM and Pre Diabetes was 13.2% (n, 26) and 9.0% (13), respectively using FPG levels among stress hyperglycemic patients. The Frequency of STEMI, nSTEMI and Unstable angina was 59.7% (n, 166), 19.4% (n, 54) and 21% (n, 58), respectively. Conclusion: There is higher prevalence of stress hyperglycemia and known diabetes mellitus with small number of incident diabetes in the present study.